Formulasi Kebijakan Pendidikan Karakter dalam Perspektif Perubahan Sosial - Yakin, Nurul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
Character education is an effort to internalize the nation's character in students based on noble values ​​and norms that exist in society. To be able to realize a strong character education system, a good policy formulation is needed. Policy formulation needs to accommodate all matters, especially those related to community social behavior. This discussion seeks to reveal how the character education policy should be carried out, as well as how relevant and contextualized it is to changes that occur in the social environment. The research method used in this research is a qualitative approach with library research type. This study concludes that character education policies with the paradigm of social change must be based on Pancasila, Bhinika Tunggal Ika and the applicable legal system. Culture, tradition, and local wisdom of the Indonesian nation should become a reference pillar in the context of policy formulation because it is an inherent part of character education. Character education is very important because social change for the better is strongly influenced by the quality of society, while the quality of society is influenced by the pattern of education provided